MARKET ORIENTATION IN NIGERIAN INSURANCE FIRMS: A RESEARCH AGENDA - Osuagwu, Caroline (Archives of Business Research, 2019)
Market orientation is the business philosophy that sees the customer as the centre of business activities. Therefore, organizations, including insurance firms, require the practice of market orientation in order to achieve organizational efficiency and performance indices. The proposed research aims to examine the emphases, dimensions and performance impacts of market orientation in Nigerian insurance firms. Using a mix of qualitative and quantitative research approaches, the proposed research intends to provide insights into the above-stated market orientation issues in a sample of Nigerian insurance firms. The findings from the research are likely to have managerial relevance in Nigerian insurance firms, in addition to assisting government policies and interventions aimed at improving the growth and development of the Nigerian insurance sector. Also, the proposed research would add to relevant literature and encourage future research efforts in related areas of insurance management in Nigeria and other developing economies, especially in sub-Saharan Africa.